A decentralized lightweight authentication protocol under blockchain. (4th April 2022) - Xu, Mingcheng; Xu, Gaojian; Xu, Haoyu; Zhou, Jiadong; Li, Shaowen
Abstract: With the continuous development of blockchain technology, blockchain gradually becomes to play an important role in the fields of finance, medicine, and new energy. In the certification of the membership of the blockchain, a third‐party certificate authority (CA) is used for certification. Considering the centralized structure of CA, and it is difficult for users to evaluate the credibility of CA. A decentralized blockchain membership authentication scheme and a key agreement protocol based on the elliptic curve are proposed by us. The protocol effectively addresses the credibility and single point of failure problems of centralized CAs in the traditional model. Through analysis, our scheme can effectively perform user registration and membership authentication instead of CAs. The security and correctness of the protocol was also analyzed using the formal protocol analysis tool ProVerif and the Ck model. The key authentication protocol we proposed can resist a variety of attacks, and the computational time consumption and Communication costs are relatively low.